UJI AKTIVITAS ANTIBAKTERI SEDIAAN EMULGEL EKSTRAK BELIMBING WULUH (Averrhoa bilimbi L.) TERHADAP BAKTERI Propionibacterium acnes - Sholaekah, Ayu; Hidayati, Evi Nurul; Sardjiman (APDFI (Asosiasi Pendidikan Diploma Farmasi Indonesia), 2025)
Acne is a condition of sebaceous follicle disruption caused by keratinization disorders (small keratosis), accompanied by the presence of comedones, papules, pustules, and nodules. Starfruit (Averrhoa bilimbi L.) harbors compounds exhibiting antibacterial properties against Propionibacterium acnes, making it a promising candidate for developing an anti-acne emulgel product. The starfruit was extracted via maceration using 70% ethanol solvent over 3x24 hours. Test samples of starfruit extract were prepared at concentrations E1 (10%), E2 (15%), and E3 (20%), while emulgel formulations of the extract were formulated as F1 (10%), F2 (15%), and F3 (20%). Physical evaluations included organoleptic, adhesion, spreadability, homogeneity, pH, emulgel type assessments, and antibacterial tests measuring inhibition zones. Inhibition zone data were analyzed using ANOVA statistics. The method used to observe antibacterial activity in the emulgel formulations employed the good diffusion method by measuring inhibition zone diameters around the holes. The results of antibacterial activity testing of starfruit extract emulgel formulations against Propionibacterium acnes sequentially in F1, F2, F3, K+, K- were 11.96 ± 0.38 mm (strong), 13.84 ± 0.50 mm (strong), 15.03 ± 0.56 mm (strong), 17.64 ± 0.69 mm (strong), and 0 ± 0.00 mm (no antibacterial activity). The evaluation results of the physical quality of starfruit extract emulgel formulations indicated that all three formulas exhibited good physical quality. Based on the study findings, F3 demonstrated superior inhibitory efficacy among the emulgel formulations.